Production optimation of clones slow starter IRR 42 application through stimulant etefon - Yayuk Purwaningrum; . Junaidi; Lollie Agustina (Syiah Kuala University, 2013)
IRR 42 clones belonging to clone a slow starter who has good growth and great girth, but production of the rubber tends to be low when compared to other superior clones. This study aims to obtain stimulant treatment may be able to optimize the production potential clones IRR 42. The research wasconducted at the Research Institute for Experimental Sungei White, Rubber Research Center for four months (May-August 2012) in the area of crop planting clones IRR 42 years in 2006 (6 years old plants). The treatments tested include concentration of stimulant (S) consisting of 1.25%, 2.50%, 3.50% and 4.50%,treatment application interval (W) consists of one and two times per month as well as application control treatment (without stimulants). The results showed an average production of 2.50% on stimulant treatment and 4.50% at intervals of twice per month (S2W2 and S4W2) have higher production compared with other treatments. In general, plant physiology is still below the threshold. S2W2 treatment is the best treatment to optimize the potential of the plant because it has high production but showed lower stress than the exploitation S4W2. Further research is needed in a longer period of time to determine plant responses to each treatment